Virginia at war, 1862 - Davis, William C., 1946-; Robertson, James I., Jr. (James Irvin), 1930-2019 (Virginia at war series., 2007)
A History Book Club SelectionA Military History Book Club Selection Virginia emerged from the year 1861 in much the same state of uncertainty and confusion as the rest of the Confederacy. While the North was known to be rebuilding its army, no one could be sure if the northern people and government were willing to continue the war. Virginians' expectations for the coming year did not prepare them for what was about to happen, for in 1862 the war became earnest and real, and the Old Dominion became then and thereafter the major battleground of the war in the East.